Nutritional Supplementation in HIV-Infected Children: A Review - Siyazi Mda (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2015)
The nutritional status of HIV-infected children in terms of anthropometric indices and micronutrient concentrations is commonly compromised. Malnutrition is a risk factor for mortality at initiation of highly active antiretroviral therapy (HAART). The role of HAART is pivotal in the management of HIV-infected children. Treatment with HAART has been shown to decrease mortality and improve CD4 counts and reduce viral load. HAART has beneficial effects on the nutritional status as well. However, childrenwho are severely malnourished have an increased risk of mortality when initiating HAART. A number of studies have thus assessed whether supplementation with macronutrients and micronutrients would improve the nutritional status and reduce morbidity and mortality in these children. Supplementation with macronutrients seems to improve energy intake and initially improves weight gain but seems to have no effect on morbidity and mortality. Micronutrient supplementation has been shown to improve weight and reduce diarrhoeal and respiratory morbidity. Serious consideration should be given to supplementing both macronutrients and micronutrients in children initiating HAART.